Emergency room intervention to prevent post concussion-like symptoms and post-traumatic stress disorder. A pilot randomized controlled study of a brief eye movement desensitization and reprocessing intervention versus reassurance or usual care. (August 2018) - Gil-Jardiné, Cédric; Evrard, Grégoire; Al Joboory, Samantha; Tortes Saint Jammes, Juliane; Masson, Françoise; Ribéreau-Gayon, Régis; Galinski, Michel; Salmi, Louis-Rachid; Revel, Philippe; Régis, Cyril Alexandre; Valdenaire, Guillaume; Lagarde, Emmanuel
Abstract: Up to 20% of patients presenting at an emergency room (ER) after a stressful event will for several months suffer from very diverse long-lasting symptoms and a potentially significant decline in quality of life, often described as post concussion-like symptoms (PCLS). The objectives of our randomized open-label single-center study were to assess the feasibility of psychologist-led interventions in the context of the ER and to compare the effect of eye movement desensitization and reprocessing (EMDR) with reassurance and usual care. Conducted in the ER of Bordeaux University Hospital, the study included patients with a high risk of PCLS randomized in three groups: a 15-min reassurance session, a 60-min session of EMDR, and usual care. Main outcomes were the proportion of interventions that could be carried out and the prevalence of PCSL and post-traumatic stress disorder (PTSD) three months after the ER visit. One hundred and thirty patients with a high risk of PCLS were randomized. No logistic problem or patient refusal was observed. In the EMDR, reassurance and control groups, proportions of patients with PCLS at three months were 18%, 37% and 65% and those with PTSD were 3%, 16% and 19% respectively. The risk ratio for PCLS adjusted for the type of event (injury, non-injury) for the comparison between EMDR and control was 0.36 [95% CI 0.20–0.66]. This is the first randomized controlled trial that shows that a short EMDR intervention is feasible and potentially effective in the context of the ER. The study was registered atClinicalTrials.gov (NCT03194386).